2015
DOI: 10.1103/physreve.92.062712
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA binding sites and slow unbinding kinetics in titration-based oscillators

Abstract: Genetic oscillators, such as circadian clocks, are constantly perturbed by molecular noise arising from the small number of molecules involved in gene regulation. One of the strongest sources of stochasticity is the binary noise that arises from the binding of a regulatory protein to a promoter in the chromosomal DNA. In this study, we focus on two minimal oscillators based on activator titration and repressor titration to understand the key parameters that are important for oscillations and for overcoming bin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…In the work of Jayanthi et al [ 36 ], it was shown that one can deal with retroactivity in a simple manner by tuning the periods and amplitudes of model synthetic oscillators by adding more copies of the operators. The related work by Karapetyan et al [ 37 ] shows that adding a small number of operators can increase the coherence of generic activator and repressor oscillators. While adding operators can be a very effective means for reducing the dichotomous noise and directly changing the delay in the feedback loops, this multiplication of resources may not be effective for circuits that have a large number of targets as is the case of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…In the work of Jayanthi et al [ 36 ], it was shown that one can deal with retroactivity in a simple manner by tuning the periods and amplitudes of model synthetic oscillators by adding more copies of the operators. The related work by Karapetyan et al [ 37 ] shows that adding a small number of operators can increase the coherence of generic activator and repressor oscillators. While adding operators can be a very effective means for reducing the dichotomous noise and directly changing the delay in the feedback loops, this multiplication of resources may not be effective for circuits that have a large number of targets as is the case of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…The second model is called a repressor-titration circuit (RTC) because X is a transcriptional repressor [ 15 ] ( figure 1 b ). This model differs from the ATC in two ways.…”
Section: Mathematical Frameworkmentioning
confidence: 99%
“…The PDMP framework will now be applied to more sophisticated models of the ATC. A previous model of the ATC [ 15 ], which we call the KB model, showed that multiple binding sites lengthened the period and improved coherence of stochastic cycling. Using the PDMP, we will show that multiple binding sites per se are insufficient to improve coherence.…”
Section: Analyses Of More Detailed Mechanistic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the synthetic biology context designing ways to enhance coherence or reducing the dichotomous noise of promoter binding is one of the main challenges for modular design of functional circuits [14]. So far this problem of engineering modular circuits has been combatted in a brute force fashion by increasing the cooperative association of proteins with DN A or by adding more copies of the promoter sites [14][15][16].…”
Section: Introductionmentioning
confidence: 99%